Consumer Satisfaction at Coffee Shop Pintu Dua Jakarta is Influenced by Store Atmosphere and Product Quality Through Price - Haryanto, Aji; Sanusi, Eddy; Utomo, Fajar Cahyo (Dinasti International Journal of Management Science, 2025)
The purpose of this research is to determine the influence of customer satisfaction at Coffee Shop Pintu Dua Jakarta, which is affected by store atmosphere and product quality through pricing. The research method used is multiple linear regression to analyze the impact of independent variables on the dependent variable, as well as the Sobel test to analyze the effect of the price mediation variable. The data used is primary data obtained from consumer responses to questionnaires. The results show that, partially, store atmosphere has a significant positive effect on customer satisfaction, as does product quality, which also has a significant positive effect on customer satisfaction. Price mediates the effect of store atmosphere on customer satisfaction, and it also mediates the effect of product quality on customer satisfaction.